2003
DOI: 10.1115/1.1565081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiative Transfer Modeling on Transient Temperature Distribution in Semitransparent Glass Rod

Abstract: This paper presents a method of modeling the radiative energy transfer that takes place during the transient of joining two concentric, semitransparent glass cylinders. Specifically, we predict the two-dimensional transient temperature and heat flux distributions to a ramp input which advances the cylinders into a furnace at high temperature. In this paper, we discretize the fully conservative form of two-dimensional Radiative Transfer Equation (RTE) in both curvilinear and cylindrical coordinate systems so th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…Homsy and Walker [10] found that the Rosseland diffusion approximation, which is an assumption commonly used in many early studies in solving the radiative transfer in the semitransparent glass, would fail at the surface. This finding was confirmed in a similar study [1], where the radiative transfer equation (RTE) was numerically solved using discrete ordinate method (DOM) to predict the temperature gradient built up during transient. The analysis in [1] further showed that the glass absorption coefficient in the short-wavelength band cannot be neglected and proposed a modified band model that includes the glass absorption at short wavelengths.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Homsy and Walker [10] found that the Rosseland diffusion approximation, which is an assumption commonly used in many early studies in solving the radiative transfer in the semitransparent glass, would fail at the surface. This finding was confirmed in a similar study [1], where the radiative transfer equation (RTE) was numerically solved using discrete ordinate method (DOM) to predict the temperature gradient built up during transient. The analysis in [1] further showed that the glass absorption coefficient in the short-wavelength band cannot be neglected and proposed a modified band model that includes the glass absorption at short wavelengths.…”
Section: Introductionsupporting
confidence: 73%
“…This finding was confirmed in a similar study [1], where the radiative transfer equation (RTE) was numerically solved using discrete ordinate method (DOM) to predict the temperature gradient built up during transient. The analysis in [1] further showed that the glass absorption coefficient in the short-wavelength band cannot be neglected and proposed a modified band model that includes the glass absorption at short wavelengths. Another approach, the finite volume method (FVM), has been investigated for modeling semitransparent, emitting, and absorbing medium.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The water content in glasses may vary in a very wide range [5,16] so that investigations of temperature distributions at different values of water concentrations in the layer are carried out. It is established that the presence of water influences the temperature field and the effect is maximum at certain value of water concentration.…”
Section: Effect Of Water Impurity On the Temperature Fieldmentioning
confidence: 99%
“…Its spectral absorption coefficient is given as follows [16] a M λ = a 1 , 0.2 λ 2.8 µm a M λ = a 2 , 2.8 λ 4.8 µm a M λ = a 3 , 4.8 < λ µm It was shown recently [16] that accounting for absorption in the range 0.2 λ 2.8 µm is important for the accurate prediction of the temperature field in the fiber drawing process, despite low values of the absorption coefficient in this range. Five bands model for water absorption [13] was considered here.…”
Section: Computational Experimentsmentioning
confidence: 99%